PENGEMBANGAN VIDEO PEMBELAJARAN BAHASA INDONESIA TEKNIK MEMBACA PUISI - Marius Panje; Sihkabuden Sihkabuden; Anselmus J. E Toenlioe (Pascasarjana Universitas Negeri Malang, 2016)
Instructional Technology born out of the reality of education and movement of audio-visual communication. Instructional Technology originally envisioned as technological equipment, related to the use of equipment, media and the means to achieve the goal of education or in other words teaching with audio-visual aids. One of the media that is based on audio-visual media video. The lesson of Indonesian and Indonesian Literature, learning-oriented nature of Indonesian and Literature, which states that learning Indonesian is learning to use the language correctly. In Indonesian, there is a sub-science that is often called the study of literature. One of the lessons learned from the study of literature is poetry. This study is conducted to examine the poetry reading techniques. The purpose of this study are: 1) to produce a video about learning to read poetry in Indonesian; 2) to know the level of validation of videos product about reading poetry; 3) to know the result of learning of the students who use the media of instructional video. This study uses the method of qualitative descriptive and uses the model Borg and Gall to answer the questions above. In this case, the researcher as an observer and the teacher as facilitator of learning in the classroom. In collecting the data through observation, the researcher uses a tape recorder, the guide of interview. The result shows that the result of expert communication media is valid / feasible to use in the learning process and based on the result of a value obtained results vaidasi 91.25%. The result of the experts in the field is valid / feasible to use in the learning process, and based on the results obtained vaidasi a value of 85%. The results of the audience / the students on a limited scale is valid / feasible to use in the learning process, and based on the results obtained vaidasi worth 91.7%. The results of the audience / the students of the fieldtest is valid / feasible to use in the learning process, and based on the results vaidasi value of 85.1%. The results of the test are limited to substantially increase learning outcomes trials. The increasing of the learning result can be evidenced before the students using the means of instruction, the graduation rate was 33.3%, and after the students using instructional media, presentations graduation increased to 100%. The result of field tests have increased on the result of learning. The result of the increased learning, can be evidencedbefore the students using the means of instruction, the graduation rate is 5%, and after students using instructional media, presentations graduation increased to 85%. Therefore, the learning media can be used in the process of learning to improve learning outcomes for students. Teknologi Pembelajaran lahir dari realita pendidikan dan gerakan komunikasi audio visual. Teknologi Pembelajaran semula dilihat sebagai teknologi peralatan, yang berkaitan dengan penggunaan peralatan, media dan sarana untuk mencapai tujuan pendidikan atau dengan kata lain mengajar dengan alat bantu audio-visual. Salah satu media pembelajaran yang berlandaskan audio-visual adalah media video. Mata pelajaran Bahasa dan Sastra Indonesia, berorientasi pada hakikat pembelajaran Bahasa dan Sastra yang menyatakan bahwa, belajar bahasa Indonesia adalah belajar menggunakan bahasa yang baik dan benar. Dalam pelajaran Bahasa Indonesia, terdapat sub ilmu yang sering disebut dengan pembelajaran sastra. Salah satu pembelajaran yang dipelajari dalam pelajaran sastra adalah puisi. Penelitian ini dilaksanakan untuk meneliti teknik membaca puisi. Tujuan penelitian ini adalah 1) menghasilkan produk video tentang membaca puisi dalam pembelajaran Bahasa Indonesia; 2) mengetahui tingkat validasi dari produk video tentang membaca puisi; 3) mengetahui hasil belajar siswa dengan menggunakan media video pembelajaran. Penelitian menggunakan rancangan metode deskriptif kualitatif dan menggunakan model penelitian pengembangan Sadiman, untuk menjawab pertanyaan di atas. Dalam hal ini, peneliti sebagai observer dan guru sebagai fasilitator dalam pembelajaran di dalam kelas. Dalam mengumpulkan data melalui observasi, peneliti menggunakan alat perekam, pedoman wawancara. Hasil penelitian menunjukkan bahwa hasil yang diperoleh dari ahli media adalah valid/ layak digunakan dalam proses pembelajaran dan berdasarkan hasil vaidasi diperoleh nilai sebesar 91,25%. Hasil yang diperoleh dari ahli materi adalah valid/ layak digunakan dalam proses pembelajaran, dan berdasarkan hasil vaidasi diperoleh nilai sebesar 85%. Hasil yang diperoleh dari audiens/ siswa dalam skala terbatas adalah valid/ layak digunakan dalam proses pembelajaran, dan berdasarkan hasil vaidasi diperoleh nilai sebesar 91,7%. Hasil yang diperoleh dari audiens/ siswa uji lapangan adalah valid/ layak digunakan dalam proses pembelajaran, dan berdasarkan hasil vaidasi diperoleh nilai sebesar 85,1%. Hasil tes uji coba skala terbatas mengalami peningkatan hasil belajar. Peningkatan hasil belajar tersebut dapat dibuktikan ketika siswa sebelum menggunakan media pembelajaran, persentasi kelulusannya adalah 33,3%, dan setelah siswa menggunakan media pembelajaran, presentasi kelulusannya meningkat menjadi 100%. Hasil tes uji lapangan mengalami peningkatan hasil belajar. Peningkatan hasil belajar tersebut, dapat dibuktikan ketika siswa sebelum menggunakan media pembelajaran, persentasi kelulusannya adalah 5%, dan setelah siswa menggunakan media pembelajaran, presentasi kelulusannya meningkat menjadi 85%. Dengan demikian, media pembelajaran ini dapat digunakan dalam proses pembelajaran untuk meningkatkan hasil belajar siswa.